Penerapan Pendidikan Akhlak Murid Perempuan Dalam Kitab Akhlak lil Banat - Haerunnisa Haerunnisa; Muhammad Yasin; M. Farid Wajdi (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
Moral education is one way to guide someone in good behavior. In an educational institution, there must be coaching or education for the morals of the students. At Darul Hikmah Islamic Boarding School, moral education for students uses the teaching of classical books, one of which is the book of Akhlaqu lil banat volume I. The aims of this study are: 1) To determine the moral education of female students in the book Akhlaqu lil banat volume I and 2) to find out the implementation and evaluation of female students' moral education at the Darul Hikmah Islamic Boarding School. This study uses a qualitative approach with a descriptive method. Data collection techniques used in this study were observation, interviews and documentation. The results of the study show that: 1) In the book of Akhlaqu lil banat volume I there is a lot of moral education for girls, from childhood to adulthood and there are things that girls can and cannot do. 2) The application of moral education for female students contained in the book Akhlaqu lil banat volume I has had a good influence on the moral formation of female students in Darul Hikmah Islamic boarding schools. Changes that can be seen from the 7th grade female students are changes in behavior (polite) and in speaking or speaking well to teachers, older people or to their friends. Keywords: Moral Education